Who does most of the work? High self‐control individuals compensate for low self‐control partners. (14th May 2019) - van Sintemaartensdijk, Iris; Righetti, Francesca
Abstract: Accomplishing goals with others can be troublesome. Some people may work extra hard while others do much less. When does this workload asymmetry occur? The present research investigates the role of perceived partners' self‐control in workload distribution. Specifically, we tested the hypothesis that high self‐control individuals work harder and compensate when they work together with low self‐control partners. Results from two studies indicate that high self‐control individuals are sensitive to their partners' level of self‐control and adjust their behavior accordingly (i.e., exerting extra effort) when working with them.